Maternal and newborn health indicators in Papua New Guinea – 2008–2018. Issue 1 (1st January 2019) - Robbers, Gianna; Vogel, Joshua P.; Mola, Glen; Bolgna, John; Homer, Caroline S. E.
Abstract: Papua New Guinea (PNG) is the most populous country in the Pacific with more than 9 million people. Difficult terrain, poor roads and limited infrastructure mean providing effective health care – especially in rural areas, where most people live – is challenging. Women and newborns in PNG experience high rates of preventable morbidity and mortality; however, reliable data are often limited or unavailable. The aim of this paper is to provide an overview of research on key maternal and neonatal health (MNH) indicators conducted approximately over the past 11 years in PNG comparing research findings to global MNH estimates of the indicators. There was considerable variation in mortality indicators (maternal mortality ratio, neonatal mortality rate and stillbirth) reported across studies in PNG. Mortality was generally higher in rural areas. Rates of sexually transmitted infections (STIs) in pregnancy were consistently high, while anaemia in pregnancy, preterm birth and low birth weight varied widely between studies and settings. Breastfeeding seems to have been under-researched. There was a lack of data available on other indicators such as the adolescent birth rate, postnatal care provided to women and newborns, intermittent preventative treatment to prevent malaria in pregnancy and treatment to prevent mother-to-child transmission of HIV. Studies demonstrate the high burden of preventable maternal and newborn morbidity and mortality across PNG. Efforts to improve MNH outcomes need to be escalated.